Omalizumab and other biologics in drug desensitization. Issue 4 (August 2020) - Fernandez, Javier; Ruano-Zaragoza, María; Blanca-Lopez, Natalia
Abstract : Purpose of review: Omalizumab has been proposed for controlling adverse reactions during drug desensitization. Our aim is to know the current evidence involving the use of omalizumab in drug-allergy desensitization. Recent findings: Drug-allergy desensitization is not risk free, but it is a useful procedure and has been applied for drug hypersensitivity reactions with mast cells degranulation through IgE and non-IgE mechanisms. Since 2007, omalizumab has been considered as a potential strategy to prevent adverse reactions. Our review found few case reports and only one randomized double-blind, placebo-controlled study, using different omalizumab regimens prior to drug desensitization. This scarce evidence is insufficient to predict the effectiveness of omalizumab in rapid drug desensitization procedures, but it may be useful in future studies of omalizumab or related next-generation antibodies. Summary: Omalizumab or other IgE-targeting biologics, either a fixed dose of 300 mg omalizumab or a dose-related total IgE level and body mass weight may be an option for patients with IgE-mediated or mast cell drug reactions in troublesome desensitization.